Integration of Blue Ocean Strategy of Build Your Dream (BYD) Co. Ltd to the Sustainability Principles of the Electric Vehicle Industry in International Market Expansion: - - Dwi Asri Leolita (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
The electric vehicle industry is growing worldwide, and BYD Co. Ltd is one of the leading company in this industry. However, in international market expansion, companies need to pay attention to the principle of sustainabilityto ensure that their business is sustainable and does not harm the environment. This study aims to analyze the integration towards the sustainability principle of the electric vehicle industry in international market expansion. This research will use SWOT analysis to explore the macro environment and development prospects of BYD. To analyze the case study, researchers use secondary data sources through the collection of various sources from journals and scientific literacy and articles both online and in print that are credible and can be accounted for their validity. The results of this study are expected to provide a better understanding of how the integration of Blue Ocean Strategy and BYD can affect the sustainability principles of the electric vehicle industry in international market expansion and provide useful recommendations for BYD in developing its business in the international market. The hypothesis in this study is that the integration of Blue Ocean Strategy and BYD can influence the sustainability principles of the electric vehicle industry in international market expansion through the development of more efficient and environmentally friendly electric vehicles. In other words, the integration of sustainability principles in electric vehicle production can strengthen BYD’s position as a leader in the sustainable electric vehicle industry in the international market.